ANALISIS PENGARUH ADANYA FAKTOR HARGA, KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada UD. Ikan Mas di Kabupaten Pemalang) - Afrian, Reza; Sutopo, Sutopo (Diponegoro Journal of Management, 2017)
This research aims to determine whether price, product quality and brand image influence the purchase decisions in UD. Ikan Mas. This research is motivated by a decrease in the number of consumer and selling intensity in UD. Ikan Mas.The populations used in this research was a UD. Ikan Mas Consumer. The collection of data by using a questionnaires with a number of samples 100 respondents who buyed product in UD. Ikan Mas. This research method, using the technique of non-random sampling with purposive sampling method. Data obtained from questionnaires, then processed and analyzed using multiple linear regression analysis through the SPSS 23 software.Based on the result of the research, it was found the regression equation as follows:Y = 0,384 X1 + 0,238 X2 + 0,312 X3The result of this research shows that all independent variables are the price, product quality and brand image has a positive effect on the dependent variable that is the purchase decision by using T test. Then through F test shows that the three independent variables are proper to examine the dependent variable. Adjusted R Square of 0,753 shows that the independent variables can explain 75,3% the dependent variable that is purchase decision, while the remaining 24,7% is explained by other variables outside of variable that used in this research.